Towards a new methodology for working with historic theatre costume: A biographical approach focussing on Ellen Terry's 'Beetlewing Dress'. Issue 2 (1st September 2017) - Isaac, Veronica
Direct engagement with the material culture of historic theatre costume, particularly surviving costumes, has the potential to make a significant contribution to the existing discourse surrounding costume and performance. The comparative absence of the surviving costumes from such discussions stems in part from the fact that the value of this source material has yet to be fully recognized, researched and theorized. Responding directly to that challenge, this article unites approaches from dress history, theatre history and material culture to offer a specific methodology for the investigation and analysis of theatre costume, which is founded upon the examination and assessment of such garments. Nineteenth-century actress Ellen Terry (1847–1928) will be used as a case study through which to present this new methodology. Most famous for the 22 years she spent as the leading lady of the Lyceum Theatre, this discussion will focus on one of Terry's more celebrated Shakespearean roles, Lady Macbeth. It will explore the design, creation and afterlife of costumes worn by Terry in the 1888 Lyceum production of Macbeth, and consider the crucial part they played, not simply in the original staging, but also in shaping the legacy of both performance and performer. The close analysis of this key example from Terry's theatrical wardrobe will establish the factors fundamental to the interpretation of such garments and demonstrate the evidence offered from material culture sources, most importantly, surviving costumes. Through this discussion, the article will offer a new methodology for the analysis of historic theatre costume, which can be employed in the study of other figures, theatres and periods, opening up a new and productive direction for future research.